1998
DOI: 10.1046/j.1365-3083.1998.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐Cell Clonal Change after Allo‐Kidney Transplantation in Humans

Abstract: Whether T cells circulating peripherally express changes at a clonal level after renal transplantation is uncertain. To clarify this issue, we analyzed T-cell clonality of peripheral blood lymphocytes (PBLs) in 12 renal transplant recipients by a novel polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) method that can discriminate T-cell clones with different T-cell receptor (TCR) Vb motifs. The PCR-SSCP study showed that after transplantation, only a few distinct T-cell clonotypes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Some similarities but also some differences in predominant V␤ gene usage were noted between GIL and MLC populations (20).…”
Section: V␤23mentioning
confidence: 88%
“…Some similarities but also some differences in predominant V␤ gene usage were noted between GIL and MLC populations (20).…”
Section: V␤23mentioning
confidence: 88%
“…Owens et al (25) suggested that the establishment of short-term stable renal allograft function (1 year posttransplantation) requires the deletion of certain T cells from peripheral blood. Whereas many studies described TCR usage during graft rejection in humans (14,(26)(27)(28)(29), to our knowledge, no studies on TCR usage in long-term functioning kidney transplants have hitherto been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Clonality of T cells has been analyzed by Southern blot hybridization (27), CDR3 length analysis (15), and single-strand conformation polymorphism (28). We analyzed TCR repertoires in a quantitative fashion and clonal T-cell expansion in the TCRBV segments in the present study.…”
Section: Relationship Between Clonal T-cell Expansion and The Functiomentioning
confidence: 99%
“…Hagihara et al demonstrated that clonal expansion of T cells occurred in peripheral blood at an early period after kidney transplantation using the PCR single-strand conformation polymorphism method (28). They reported that various T-cell clones appeared in the recipients with an acute rejection of the transplanted kidney and a viral infection.…”
Section: Relationship Between Clonal T-cell Expansion and The Functiomentioning
confidence: 99%